Large scale analysis of amino acid substitutions in bacterial proteomics. Issue 1 (December 2016) - Ischenko, Dmitry; Alexeev, Dmitry; Shitikov, Egor; Kanygina, Alexandra; Malakhova, Maja; Kostryukova, Elena; Larin, Andrey; Kovalchuk, Sergey; Pobeguts, Olga; Butenko, Ivan; Anikanov, Nikolay; Altukhov, Ilya; et al.
Abstract Background Proteomics of bacterial pathogens is a developing field exploring microbial physiology, gene expression and the complex interactions between bacteria and their hosts. One of the complications in proteomic approach is micro- and macro-heterogeneity of bacterial species, which makes it impossible to build a comprehensive database of bacterial genomes for identification, while most of the existing algorithms rely largely on genomic data. Results Here we present a large scale study of identification of single amino acid polymorphisms between bacterial strains. An ad hoc method was developed based on MS/MS spectra comparison without the support of a genomic database. Whole-genome sequencing was used to validate the accuracy of polymorphism detection. Several approaches presented earlier to the proteomics community as useful for polymorphism detection were tested on isolates ofHelicobacter pylori, Neisseria gonorrhoeae andEscherichia coli . Conclusion The developed method represents a perspective approach in the field of bacterial proteomics allowing to identify hundreds of peptides with novel SAPs from a single proteome.